Fotorreatividade e biodisponibilidade da matéria orgânica dissolvida produzida por Microcystis aeruginosa - Bittar, Thais Beraldo (Universidade Federal de São Carlos, 2010)
Photochemically and biologically mediated reactions are key processes on the transformation of dissolved organic matter (DOM) in natural waters. The aims of this study were to evaluate these isolated and coupled processes over the DOM produced by the Cyanobacteria Microcystis aeruginosa, which contributes with great amounts of biomass in the Barra Bonita Reservoir. Our results showed that photodegradation occurred, but also showed that there were cyanobacterial photoresistant molecules and photoproducts that were identified in the Reservoir s DOM. Pre exposure of the DOM released by M. aeruginosa caused decrease in bioavailability of this type of DOM due to competition, i.e., removal of the biolabile portion of the DOM by irradiation. The bioavailability of intracellular DOM was not significantly altered by pre exposure to UV radiation. Detailed chemical characterization showed that competition between photo and biodegradation and photoproduction of biolabile compounds, equilibrated negative and positive effects of irradiation on the bioavailability of the intracellular DOM.
Keywords: Ficologia; Biodisponibilidade; Radiação ultravioleta; Matéria orgânica dissolvida; Cianobactéria; Bacterioplâncton; CIENCIAS BIOLOGICAS::ECOLOGIA